Iron-Promoted 1,5-Substitution Reaction of Endocyclic Enyne Oxiranes With Memgbr: a Stereoselective Method for the Synthesis of Exocyclic 2,4,5-Trienol Derivatives - Kuş, Melih; Artok, Levent; Omur, Cenk; Kuş, Melih; Karaca, Sila; Artok, Levent (MDPI, 2023)
The iron-promoted 1,5-substitution reaction of endocyclic oxiranes with MeMgBr yields exocyclic 2,4,5-trienols with high diastereomeric ratios of up to 100:0. However, for the method's success, the oxirane ring must have a trans-configuration. The reactions exhibit strong stereoselectivity concerning the methylation mode and the configuration of the resulting exocyclic double bond. Enantiomerically pure enyne oxiranes can be synthesized through Sharpless asymmetric dihydroxylation and subsequent manipulations. With these reagents, it has been possible to produce exocyclic 2,4,5-trienols in enantiopure forms. Importantly, this process maintains chirality without degradation during the center-to-axis transfer of chirality.
Keywords: enyne oxiranes; vinylallenes; 2,4,5-trienols; iron-catalyzed; 1,5-substitution; enantiopure allenes; Palladium-Catalyzed Alkoxycarbonylation; Electrocyclic Ring-Closure; Enantioselective Synthesis; Asymmetric Epoxidation; Grignard-Reagents; Diastereoselective Method; Propargyl Carboxylates; Conjugate Addition; Coupling Reactions; Hydrogen Shifts